Observations of condensation nuclei in the Airborne Antarctic Ozone Experiment - Implications for new particle formation and polar stratospheric cloud formation - Wilson, J. C.; Loewenstein, M.; Fahey, D. W.; Gary, B.; Smith, S. D. (1989)
This paper discusses the results of the ER-2 Condensation Nucleus Counter operated in the Airborne Ozone Experiment in August, September, and October 1987, providing data on the mixing ratio of aerosol condensation nuclei (CN) with diameters between about 0.02 and 1 micron. It is shown that the vertical profile of the CN mixing ratio is closely related to that of N2O, and that, between the -71 and -53 deg latitude, the location of the minima in the CN mixing ratio profile was near the 160 ppbv N2O isopleth, indicating that the processes of mixing and subsidence, which determine the inclination of that isopleth, also strongly affect the spatial distribution of the sulfate aerosol. Evidence for new sulfate particle formation is presented and related to the amount of subsidence experienced by air parcels in the formation of the polar vortex. Concentrations of CN are compared with those of larger particles (with diameters between 0.81 micron and 9.75 microns) to study polar stratospheric cloud formation mechanisms.